Kesiapan Sekolah Dasar Dalam Menerapkan Kurikulum Prototipe Untuk Menciptakan Generasi Yang Kreatif dan Inovatif - Nur Annisa; Primanita Sholihah Rosmana; Sofyan Iskandar; Arini Nurfadilah; Cantika Maharani (Universitas Muhammadiyah Makassar, 2022)
To determine the readiness of principals and teachers for the prototype curriculum, to find out the responses of principals and teachers to the prototype curriculum. This study adheres to the data source which was carried out by purposive sampling. In this study, the research procedure carried out was divided into three stages, namely the pre-field stage, the working stage, and the data analysis stage. Based on the results of the survey, the principals and teachers from several schools we surveyed, said that if the official prototype curriculum was used as the newest curriculum, they were ready because in the Education unit there must be periodic changes and revisions to the curriculum according to technological developments and the needs of developmental conditions and conditions. the progress of education today and also because the curriculum is a component of the guideline of educational goals that must be owned by every educational unit because education must continue to develop at all times so that there are the latest innovations in learning.